Comparing consumer liking of beef from three feeding systems using a combination of traditional and temporal liking sensory methods. (June 2023) - Corcoran, L.C.; Schlich, P; Moloney, A.P.; O'Riordan, E.; K, Millar; Botinestean, C.; Gallagher, E.; O' Sullivan, M.G.; Crofton, E.C
Graphical abstract: Highlights: Two temporal liking (TL) methods were applied to investigate the impact of animal diet on consumer liking of beef steaks. TL methods were compared to a traditional sensory method approach. The free TL method yielded more discriminative data than the structured TL and traditional method. Free TL method should be considered in future consumer studies involving beef. Abstract: Research on the effects of animal diet on consumer liking of beef has yielded conflicting results. Currently it is unknown whether dynamic changes occur in liking during consumption of beef. This study applied a combination of traditional and temporal (free and structured) liking methods to determine consumer liking of beef derived from animals that were fed grain (GF), grass silage plus grain (SG) or grazed grass (GG) during finishing. Three separate panels of beef eating consumers (n = 51; n = 52; n = 50) were recruited from Teagasc Food Research Centre, Dublin, Ireland to assess striploin steaks from animals fed either GF, SG, or GG. Using the free temporal liking (TL) method, results revealed that beef from GF animals was liked significantly less (p ≤ 0.05) in terms of overall liking, tenderness and juiciness, when compared to steaks from the SG and GG animals. These effects were not observed using the structured TL or traditional liking methods. Further analysis showed the evolution of scores over time was significant (p ≤ 0.05) for all attributes using the free TL method. Overall, the free TL method yielded more discriminative data and was perceived as easier to perform by consumers compared to the structured TL method. These results show that the free TL method may provide an opportunity to elicit more in-depth information regarding consumer sensory response to meat.